Extraction, structural properties, and applications of locust bean gum - Upadhyay M.; Kumar A.; Mishra B. (My University, 2025)
Locust bean gum (LBG) is a powdered galactomannan obtained from seed of Ceratonia siliqua, family Leguminosae. The gum shows exceptional water-holding capacity and excellent gelling strength. Due to these properties, it is widely employed in a large number of industries such as textile, paper, cosmetics, paint, food, and pharmaceuticals. Utilizing its water-retaining capacity and highly viscous nature property, numerous researches have been done on LBG to use in the field of drug delivery and in food products. This chapter focuses on the important aspects of LBG, its extraction processing, chemical composition, structural properties, and promising applications in pharmaceuticals and food industries. © 2023 Elsevier Inc. All rights reserved.